Near Symmetries: The Transnational Modernism of Edward Wolfe and William Plomer. Issue 1 (2nd January 2022) - Adler, Michelle
Abstract : Focusing on the transnational lives of William Plomer (1903–1973) and the artist Edward Wolfe (1897–1982), this paper considers the formative influences of their South African heritage on their creative development, as well as the impact of European modernism on their work. In particular, a connection is made between Wolfe's immersion in modernism and the Bloomsbury Group, and his subsequent influence on the writing of Plomer's controversial novel, Turbott Wolfe (1926), including its suppressed homoerotic elements. Finally, the paper argues that Turbott Wolfe is shaped both by Plomer's liminal position within South Africa's segregationist colonial culture, as well as by his exposure to a metropolitan modernity marked by waning confidence in the teleology of empire.